Penile size in term newborn infants - Akın, Yasemin; Ercan, Oya; Telatar, Berrin; Tarhan, Fatih (The Turkish Journal of Pediatrics, 2011)
The objective of this study was to establish standard penile size in healthy full-term Turkish newborns and to evaluate the relation between penile and other anthropometric measures. For this prospective study, stretched penile length (SPL) and penile diameter (PD) of live-borns delivered in our hospital between September 2007-December 2008 were measured, and their birthweight, length and head circumference were recorded. Penile versus other anthropometric correlations were determined by Pearson analyses, followed by linear regression. In 1217 full-term subjects, mean SPL was 3.16 +/- 0.39 cm (+/- 2.5 SD = 2.19-4.14 cm), and mean PD was 1.21 +/- 0.11 cm (+/- 2.5 SD = 0.93-1.49 cm). Linear regression analysis showed a strong correlation of SPL (p = 0.0001) to height, and PD to height (p = 0.0001) and birthweight (p = 0.002). Formulas were calculated for predicted individual values for PL and PD of newborns. In conclusion, there is a correlation between neonatal anthropometric measurements and penile anthropometry. Mean anthropometric differences of various ethnicities may account for the differences in mean SPL and PD among various ethnic populations.